Flavonoid-mediated modulation at human macrophages phospholipidome : an LC-MS lipidomics study - Conde, Tiago Alexandre Teixeira de Sousa (2018)
Macrophages are innate immune cells deeply involved in inflammation. Inflammatory signalling and macrophage lipid composition are closely related, underlying the relevance of characterising lipid alterations accompanying macrophage phenotypic and functional spectrum. Several flavonoids are recognized for their anti-inflammatory activity, although little is known about their effects towards macrophage lipid composition and metabolism. In this work, we have employed a lipidomics approach based on liquid chromatography-mass spectrometry (LC-MS) analysis of cellular lipid extracts to characterize the alterations in the phospholipidome of human macrophages (differentiated from THP-1 monocytes) in response to three flavonoids: quercetin (Que), naringin (Nar) and naringenin (Ngn). Macrophages stimulated with LPS/IFN-γ (M1) and IL-4/IL-13 (M2) were also profiled for comparison. This study enabled the identification and relative quantification of 147 phospholipids (PL) belonging to 8 different classes: phosphatidylcholines (PC), phosphatidylethanolamines (PE), lysophosphatidylcholines (LPC), lysophosphatidylethanolamines (LPE), phosphatidylglycerols (PG), phosphatidylinositols (PI), phosphatidylserines (PS) and sphingomyelins (SM). All flavonoids were seen to have a pronounced impact on the macrophage phospholipidome, causing large magnitude variations in 47-76% of all identified PL species. By comparing the most prominent effects of the three flavonoids on M1 pre-polarized macrophages, it was found that flavonoid-mediated lipid remodelling was generally characterized by increases in LPC, LPE and PG species, accompanied by decreases in choline plasmalogens and SM species, whereas the modulation of other PL species was clearly flavonoid-dependent. Overall, quercetin and naringenin shared the greatest similarity. Although it was not possible to attribute individual variations to specific biological functions, it could be concluded that flavonoids affected cell membrane composition and properties, cell signalling and communication, and, possibly, antioxidant activity. Interestingly, two species emerged as potential anti-inflammatory lipid markers of flavonoid activity, PC(32:0) and PE(O-36:6)/PE(P-36:5), decreasing in response to either M2 polarization and flavonoid treatment. Their anti-inflammatory activity and relevance to macrophage biology (e.g., membrane fluidity, production of cytokines, phagocytic capacity) should be explored in future studies. Overall, this work has shown that human macrophage phospholipidome is exquisitely sensitive to flavonoid treatment, opening new research perspectives towards a greater understanding of the interplay between flavonoid-induced PL modulation and macrophage inflammatory responses.